2018
DOI: 10.1186/s12884-018-2124-3
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after bariatric surgery: a narrative literature review and discussion of impact on pregnancy management and outcome

Abstract: Bariatric surgery (BS) is regarded to be the most effective treatment of obesity with long lasting beneficial effects including weight loss and improvement of metabolic disorders. A considerable number of women undergoing BS are at childbearing age.Although the surgery mediated weight loss has a positive effect on pregnancy outcome, the procedures might be associated with adverse outcomes as well, for example micronutrient deficiencies, iron or B12 deficiency anemia, dumping syndrome, surgical complications su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 133 publications
(216 reference statements)
2
96
0
19
Order By: Relevance
“…23 Our findings support the recommendation to avoid pregnancy in the first 1-2 years after surgery and to carefully monitor nutritional status, dietary intake, and supplementation during pregnancy. 24 Recognizing that dietary intake and composition in the first postoperative year may not reflect long-term intake, 23,25 we also assessed changes in nutritional status from 1 to 5 years to determine if risk evolves over time. The continued increase in iron, B 12 (RYGB only), vitamin D deficiencies, and abnormal PTH (RYGB only) after the first postoperative year is particularly worrisome, given the longer potential lifespan of these youth.…”
Section: Discussionmentioning
confidence: 99%
“…23 Our findings support the recommendation to avoid pregnancy in the first 1-2 years after surgery and to carefully monitor nutritional status, dietary intake, and supplementation during pregnancy. 24 Recognizing that dietary intake and composition in the first postoperative year may not reflect long-term intake, 23,25 we also assessed changes in nutritional status from 1 to 5 years to determine if risk evolves over time. The continued increase in iron, B 12 (RYGB only), vitamin D deficiencies, and abnormal PTH (RYGB only) after the first postoperative year is particularly worrisome, given the longer potential lifespan of these youth.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with mothers with the same pre-gestational BMI, BS is associated with a significantly decreased risk of macrosomia, but also with an increased risk of low birth weight. In addition, BS exposes pregnant women to the risk of nutritional deficiencies with poorly known effects in the newborn and the offspring [42]. This shows that pre-gestational weight loss may have positive effects in limiting fetal growth, but that it has to be dosed reasonably to avoid adverse effects.…”
Section: Why Haven Lifestyle Interventions Not Achieved Better Outcommentioning
confidence: 99%
“…Thus, BS may have a serious impact on these patients during the subsequent pregnancy [29]. Our review of studies demonstrated that BS has positive effects on metabolic diseases and fertility; however, it may carry medical and surgical complications for mothers and babies, such as IH, bowel intussusception, bowel obstruction, gastric band slippage, bowel volvulus, gastro-jejunal bleeding, cholelithiasis, and maternal or fetal death [28]. To minimize these adverse effects, those who undergo BS are advised to avoid pregnancy for 12-24 months after BS [30].…”
Section: Internal Herniation After Bariatric Surgerymentioning
confidence: 92%
“…Obesity is a significant health problem worldwide these days. Among the available therapeutic options for obesity, BS appears to be the best weight-reduction therapy, with a better long-term outcome [28]. A considerable number of patients undergoing BS are females in their childbearing age, and most likely, they will become pregnant in the future.…”
Section: Internal Herniation After Bariatric Surgerymentioning
confidence: 99%